Measuring Technical Efficiency of Agricultural Inputs. (January 2015) - Jain, Hansa; Jha, Ram Kumar
The increasing use of modern technological inputs like fertilizers, pesticides and manure under the condition of unstable irrigation affects the agricultural productivity. The objective of the study is to determine the technical efficiency of agricultural inputs and input–output ratio. The study is conducted in Jhansi, Lalitpur and Jalaun districts of Jhansi division in Uttar Pradesh. The sampled farms were differentiated on the basis of soil type. In order to find the technical efficiency, the Cobb-Douglas production function method was applied in which Ordinary Least Square (OLS) estimators were converted into the Corrected Ordinary Least Square (COLS) estimators. To examine the technological equality between two districts, Chow Test has been used. The selected farm size categories are marginal (up to 2.5 acre land), small (> 2.5 acre land to 5 acre land) and large (> 5 acre land).